ANALISIS EFISIENSI PRODUKSI USAHATANI BAWANG MERAH DI DESA TORONGREJO KECAMATAN JUNREJO KOTA BATU - Meing, Restituta D.A. Da; Setiaji, Jatmiko; Rofiatin, Umi Rofiatin (Universitas Tribhuwana Tunggadewi, 2024)
The objective of this study was to determine the level of technical, allocative, and economic efficiency in the utilization of production factors in shallot cultivation in Toronrejo Village, Junrejo District, Batu City. Data analysis was performed using Cobb-Douglas analysis. The results showed that the utilization of production factors simultaneously affected the production of shallots. The utilization of production factors of organic fertilizer partially affected the production of shallots. The average efficiency value of utilizing inputs such as land, seeds, organic fertilizer, inorganic fertilizer, labor, capital, and pesticides was 0.9981566. This means that the utilization of production factors must be technically efficient. The efficiency values of production factors such as land, seeds, organic fertilizers, and capital are greater than 1, which means that the means of production were not allocatively efficient. The use of production factors such as inorganic fertilizers, labor, and pesticides have efficiency values of less than 1, which means that they were not allocatively efficient. The production factors of land, seeds, organic fertilizers, and pesticides are not financially efficient, and inorganic fertilizers, labor, and capital are also not financially efficient.